Effects of dehydroabietic acid on nontarget lipidomics and proteomics of HepG2 - Xiahou, Zhikai; Han, Jun (Frontiers in Pharmacology, 2022)
Objective: It lacks studies of effects of dehydroabietic acid on multi-omics of hepatoma carcinoma cells HepG2 at present. In this study, the molecular mechanism of influences of dehydroabietic acid on HepG2 was disclosed by studying lipidomics and proteomics. Correlations among multi-omics conjoint analysis results were verified. Methods: Firstly, proteomics analysis of HepG2 was carried out through the dehydroabietic acid. Differential proteins were screened and analyzed. Pathway enrichment analyses of differential proteins were compared and the molecular mechanism was disclosed. Secondly, lipidomics analysis of HepG2 was carried out through the dehydroabietic acid. Influences of dehydroabietic acid on HepG2 were interpreted from the lipid molecular level. Finally, a conjoint analysis of data related with differentially expressed proteins of Ferroptosis and differential changing lipid molecules was implemented. Results: A total of 260 upregulated proteins and 961 downregulated proteins were screened in proteomics analysis. Top5 pathways of enrichment significant include ferroptosis, oxidative phosphorylation, protein processing in endoplasmic reticulum, and so on. In lipidomics analysis, 30 significantly differential metabolites with upregulated and downregulated expressions were identified and differentially expressed lipids were mainly related with metabolism of glyceryl phosphatide. According to the comprehensive multi-omics analysis results, real-time quantitative PCR and enzyme-linked immunosorbent assay (ELISA), ASCL3 participates in cardiolipin metabolism. Conclusions: Dehydroabietic acid influences HepG2 through the above biological pathways.